2016
DOI: 10.3171/2016.9.focus16316
|View full text |Cite
|
Sign up to set email alerts
|

Drug priming enhances radiosensitivity of adamantinomatous craniopharyngioma via downregulation of survivin

Abstract: OBJECTIVE In this study, the authors investigated the underlying mechanisms responsible for high tumor recurrence rates of adamantinomatous craniopharyngioma (ACP) after radiotherapy and developed new targeted treatment protocols to minimize recurrence. ACPs are characterized by the activation of the receptor tyrosine kinase epidermal growth factor receptor (EGFR), known to mediate radioresistance in various tumor entities. The impact of tyrosine kinase inhibitors (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Clinical data documents recurrence after radiotherapy in ACP patients . In vitro experiments support this notion, as radiation induced cell death is lower in primary ACP tumor cells where EGFR signaling is activated. This effect is maintained by the EGFR‐induced upregulation of the anti‐apoptotic protein survivin.…”
Section: Primary Cell Culture Modelmentioning
confidence: 87%
See 1 more Smart Citation
“…Clinical data documents recurrence after radiotherapy in ACP patients . In vitro experiments support this notion, as radiation induced cell death is lower in primary ACP tumor cells where EGFR signaling is activated. This effect is maintained by the EGFR‐induced upregulation of the anti‐apoptotic protein survivin.…”
Section: Primary Cell Culture Modelmentioning
confidence: 87%
“…Notably, the inhibition of EGFR signaling significantly increases irradiation susceptibility and reveals that EGFR inhibitor potency varies considerably. CUDC‐100 targeting the EGFR was shown to be much more effective than the EGFR inhibitor Gefitinib .…”
Section: Primary Cell Culture Modelmentioning
confidence: 99%
“…Here again, fractionated and hypofractionated RT were the main stimulus for increased PD‐L1 surface expression. The in vivo examinations are currently ongoing, since we are now able to locally irradiate orthotopic brain tumors …”
Section: Immunosuppression By Radiationmentioning
confidence: 99%
“…The in vivo examinations are currently ongoing, since we are now able to locally irradiate orthotopic brain tumors. 113,114 It has become obvious that besides T cell-derived IFNγ-induced expression of PD-L1, exogenous stimuli delivered by pathogen-associated molecular patterns, further cytokines and epidermal growth factor can induce surface expression of PD-L1 via multiple pathways. 115,116 With our in vitro experiments, hints were obtained that both, tumor cell-derived IFNγ and IL-6 might trigger PD-L1 expression.…”
Section: Radiation and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Although results are preliminary, they integrate the findings discussed above regarding pathologic EGFR activation, which is associated with radioresistance in other intracranial neoplasms including glioma, as well as with craniopharyngioma proliferation and recurrence, as discussed above. 29,[132][133][134][135][136] In vitro analysis demonstrated that human adamantinomatous craniopharyngioma cultures underwent significantly increased cell death when RT was preceded by tyrosine kinase inhibition using gefitinib or CUDC-101, a mechanism that was further shown to be mediated by downregulation of survivin, an established mediator of radioresistance. [135][136][137] Significant further research is required before this can be added to the clinical treatment armamentarium; notwithstanding, the optimistic preliminary results highlight a potential modality for dose minimization, enhanced local control, and decreased morbidity.…”
Section: Overview Of Radiotherapymentioning
confidence: 99%